2020
DOI: 10.1155/2020/7863243
|View full text |Cite
|
Sign up to set email alerts
|

ALDH1 Cancer Stem Cell Marker as a Prognostic Factor in Triple-Negative Breast Cancer

Abstract: Breast cancer is the most common cancer with an increasing incidence in Asia. About 20% of all breast cancers are triple-negative breast cancers (TNBCs). BCSC is a subset of tumor cells that has stem cell-like characteristics, such as a high capacity for self-renewal and tumor initiation, which implies that BCSC may cause aggressiveness of TNBC. ALDH1 has a role in early stem cell differentiation through its function in the oxidation of retinol to retinoic acid, proposed to be a strong candidate for br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…We observed that the regulatory functions of ALDH1A1 and ALDH1B1 in thyroid cancer were involved in poor outcome in patients and inhibition of TILs. ALDH1 has been reported to play a role in promoting triplenegative breast cancer progression and enhanced drug resistance in a Notch receptor 4 (NOTCH4)-dependent manner (32,33). Ciccone et al (31) observed that overexpression of ALDH1A1 was significantly associated with Vascular endothelial growth factor (VEGF)-mediated angiogenesis by retinoic acid/ Hypoxiainducible factor (HIF)-1a signal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that the regulatory functions of ALDH1A1 and ALDH1B1 in thyroid cancer were involved in poor outcome in patients and inhibition of TILs. ALDH1 has been reported to play a role in promoting triplenegative breast cancer progression and enhanced drug resistance in a Notch receptor 4 (NOTCH4)-dependent manner (32,33). Ciccone et al (31) observed that overexpression of ALDH1A1 was significantly associated with Vascular endothelial growth factor (VEGF)-mediated angiogenesis by retinoic acid/ Hypoxiainducible factor (HIF)-1a signal.…”
Section: Discussionmentioning
confidence: 99%
“…ALDH1 has been reported to play a role in promoting triple-negative breast cancer progression and enhanced drug resistance in a Notch receptor 4 (NOTCH4)-dependent manner ( 32 , 33 ). Ciccone et al.…”
Section: Discussionmentioning
confidence: 99%
“…Since p63 belongs to the p53 tumor suppressor family, and is normally expressed in the nucleus of the ME cells [151,152], an aberrant expression level or subcellular localization of p63 may signify the predisposition of cancer susceptibility or mutated suppressing genes. Previous studies have consistently revealed that the loss or cytoplasmic expression of p63 is associated with elevated stem cells, enhanced cell migration and metastasis, and increased mortality [153][154][155] [177][178][179][180][181][182][183][184][185][186][187][188][189][190][191]. Thus, the administration of these molecules, or stem cell specific inducers and stimulators to patients with a high frequency of degenerations and focal disruptions (Figure 11, 14) may facilitate the restoration of the normal replenishment and functions of the MECLs.…”
Section: Specific Applications Of Mecl In Detection and Interventions...mentioning
confidence: 96%
“…22,23 • CD117 has been specified as a leukemia CSC marker, oral squamous cell carcinoma ovarian tumors, and gastrointestinal stromal tumor. [24][25][26] • Various CSC markers have been proposed with slight alterations in protein composition and structure in breast, prostate, brain, lung, esophageal, pancreatic, colon, head, and neck cancers 27,28 (Details in Table 1).…”
Section: Surface Markersmentioning
confidence: 99%